Institutional framework in developing economies Do all dimensions matter for financial intermediation by microfinance deposit-taking institutions? - Bongomin, George O. C.; Malinga, Charles A.; Munene, John C.; Ntayi, Joseph M. (Journal of Financial Regulation and Compliance, 2018)
The purpose of this paper is to establish the relationship between institutional framework of regulative (formal rules), normative (informal norms) and cultural-cognitive (cognition), and their effects on financial intermediation by microfinance deposit taking institutions (MDIs) in developing economies like Uganda. Design/methodology/approach – Data collected from a total sample of 400 poor households and 40 relationship officers located in rural Uganda were processed using statistical package for social sciences and analysis of moment structures to establish the relationship between institutional framework of regulative, normative and cultural-cognitive, and their effects on financial intermediation by MDIs in developing economies. Findings – The results showed that the three dimensions of regulative (formal rules), normative (informal norms) and cultural-cognitive (cognition) significantly affect financial intermediation by MDIs in developing economies like Uganda. In addition, as a unique finding, two new dimensions of procedural and declarative cognition emerged from cultural-cognitive framework to determine financial intermediation among MDIs in developing economies, specifically in Uganda. Research limitations/implications – The study collected data from only poor households and relationship officers located in rural Uganda. It ignored peri-urban and urban areas in Uganda. In addition, the study focused only on MDIs and ignored other financial institutions. Besides, the study was purely quantitative, therefore, further research through interviews may be useful in future. Furthermore, the study was carried out in rural Uganda as a developing economy. Thus, future research using the same variables in other developing economies may be useful. Practical implications – Managers of
Keywords: Structural equation modeling; Developing economies; Financial intermediation; Institutional framework; Microfinance deposit taking institutions; Rules of the game